Potential utilization of air temperature, total electron content, and air relative humidity as possible earthquake precursors: A case study of Mexico M7.4 earthquake. (1st October 2022) - Salh, Hemn; Muhammad, Ahmad; Ghafar, Marjan Mohammed; Külahcı, Fatih
Abstract: This study examines ionospheric total electron content (TEC) perturbations from six International Global Navigation Satellite System stations (GNSS) including GUAT-Guatemala, SSIA-El Salvador, INEG-Mexico, MANA-Nicaragua, MDO1-United States of America, and BOGT- Colombia for several days around the occurrence of a major earthquake (M 7.4 and depth 20.0 km) in Mexico, June 23, 2020 at 10:29 Local Time (LT). The INEG station in the North-Northwest of the epicenter at a distance of about 936 km indicated a positive TEC anomaly on June 18, 2020, which can be possibly viewed as an earthquake precursor due to its occurrence during a quiet geomagnetic storm and inactive solar activity. Study findings reveal that other TEC perturbations may not be related to the earthquake, because they appeared during geomagnetic activities. Moreover, the atmospheric parameters have significant and synchronous deviations from the earthquake epicenter on June 13, 2020. The highest atmospheric chemical potential (ACP) is about 0.010 eV, atmospheric air temperature has positive deviation of 3.937 °C at 15:00 LT, the lowest atmospheric relative humidity has negative deviation of 25.387% at 13:00 LT and outgoing longwave radiation (OLR) 27.58 W m −2 . Observations validate that in the earthquake preparation zone, variations in atmospheric air temperature and relative humidity reach at peak value during 10 days prior to the impending earthquake event with the later perturbations in the ionosphere. Highlights: The relationship of TEC, Air Temp, and Relative Humidity to a major earthquake. Potential difference between stressed/unstressed rocks generates ECs along the stress grad. The Relative Humidity showed a negative anomaly above the epicenter of the EQ. A TEC anomaly is observed 1 day before the EQ during a GeoMag storms and SF. Geomagnetic Storms cause changes in the ionospheric TEC.